Koreksi Persaudaraan: Tantangan dalam Mengembangkan Hidup Bersama - Andreas Maurenis Putra (Societas Dei: Jurnal Agama dan Masyarakat, 2017)
ABSTRACT: Fraternal correction is an endeavor that will never end in life. In the diversity of the society, fraternal correction needs to be a pillar to achieve lifes goal of living together as expected through the idea of Augustine. With the reality of plurality, fraternal correction is expected to be one of the strongest foundations in spite of challenges such as differences in interpretation, communication and corrective aversion. It is difficult but necessary to be actualized because it is useful in building togetherness and bringing repentance.Â Fraternal correction is an admonition given to our neighbor to help them along the path to holiness. It is a means of spiritual progress to help us to know our defects, since these may often be hidden from us by our limitations, disguised by our self-love. It is a necessary precondition to enable us to tackle those defects with Gods help, and so improve our living. KEYWORDS: fraternal correction,